The Feasibility and Preliminary Efficacy of a School-based Intervention on the Health Cognition of Adolescents - Soyuz John; Dhanasekara Pandian; Aravind Raj Elangovan; Adhin Bhaskar (Indian Journal of Public Health, 2025)
Background: The major modifiable risk factors for noncommunicable diseases are physical inactivity, food habits, alcohol, and smoking. The risk factors typically emerge during adolescence and extend to the later years of life. Even though several structural and proximal elements decide these health-related behaviors (HRBs), the thoughts and feelings attributed to the behavior mediate the interaction between the external environment and behaviors and are amenable to change. Objectives: The current study aimed to assess whether the school-based intervention improved health cognition such as knowledge, self-efficacy, intention, and locus of control of HRBs of adolescents. Materials and Methods: We used a quasi-experimental research design. One hundred and ninety-six students from four schools in an urban district were recruited into the intervention group (n = 112) and waitlist group (n = 84). The researchers developed questionnaires to assess knowledge, self-efficacy, and intention and used the Multidimensional Health Locus of Control Scale to evaluate the participants’ locus of control. Outcomes were assessed at baseline, 1 month, and 3 months after the intervention. Results: Out of 196, 181 students completed the study. The intervention group had 106 students and waitlisted group had 76 students. Even though both groups showed improvement, Kendall’s W analysis showed that the intervention group had a higher quantum of changes in the health cognitions than the waitlisted group over time. Conclusion: School-based intervention effectively changed the adolescents’ health cognition.